Surface modifying macromolecules (SMM) - Incorporated ultrafiltration membranes for natural organic matter (NOM) removal: Characterization and cleaning - Dang, Thanh Huyen (University of Ottawa (Canada), 2009)
Membrane technology is an indispensable treatment alternative for utilities with complex water and wastewater management needs. There are a variety of state-of-art membrane solutions for potable water treatment including removing disinfection by-product (DBP) precursors, softening, acting as a physical barrier for virus, pathogens and bacteria removal, and even converting brackish groundwater and other marginal sources into safe drinking water. One of the shortcomings of membrane technology is the propensity of the membranes to become fouled. In other words, the permeate flux decreases with time and membrane surface is covered by foulants such as natural organic matter (NOM) present in water sources. Although there are different techniques used in fouling reduction, this thesis focuses only on two approaches to solve this problem; they are membrane modification and membrane cleaning. For the first approach, two types of surface modifying macromolecules (i.e., hydrophobic nSMM and hydrophilic LSMM) were employed. The key objective is to change the membrane surface characteristics to better retain the foulant and enhance water permeation. A new casting technique (called as double-pass casting method) was also developed to hopefully produce better defect-free membranes. The second approach aimed at exploring the cleaning of fouled membranes in terms of cleaning apparatus, chemicals, protocols, frequencies and the effects of membrane hydrophilicity (via additive incorporation). The membranes developed in this study were evaluated and fouled by filtering raw Ottawa River water, so the principal foulant was NOM. Blending of nSMM made the polyethersulfone (PES) membranes more hydrophobic, gave them a narrow pore size, and at the same time it hindered the penetration of water to the permeate side. Among the five modification factors studied such as polymer concentration, additive concentration, casting speed, thickness and post-treatment, only the additive concentration impacted the membrane performance (i.e., DOC removal and flux reduction) to a statistically significant level. The double-pass casting approach had a statistically significant effect on membrane morphology (smoothness of the surfaces and cross-sectional structure), and also helped increase the permeate flux and the water production but DOC rejection was lowered. It can be concluded that addition of nSMM in membrane modification is not a good choice for the purpose of treating drink water. The incorporation of LSMM showed a more promising result. The PES-LSMM membranes had the highest flux resistance and highest TOC rejection (approximately 80%) in comparison with similar commercial ultrafiltration (UF) membranes. Besides PES base polymer, the LSMM can be miscible with a lot of other base polymers such as CA, PEI, PS, PVDF. Nevertheless, only PVDF membranes apparently had benefits from this hydrophilic additive with high flux changes or water production. Four types of UF cells have been evaluated in the cleaning stage including a stirred UF cell, a SEPA cell, a single CF cell and a six-CF cell- in parallel system. The performance of the first three single cells in terms of flux was similar for the first testing cycle and then deviated in subsequent cycles due to different degree of NOM deposition and the ease of cleaning corresponding with different cell geometries. The six-cell-in-parallel system behaved quite differently from the single cell CF system. Cleaning efficiency at bench-scale had no significant difference regardless of cell type as long as a short cleaning frequency (i.e., 30 min) was employed. However, the SEPA cell is recommended for long-term cleaning test (several hours) since its design simulates better a real spiral wound membrane module with feed spacers and permeate carriers on the feed and permeate side of the membrane sheets, respectfully. The combination of backwashing and chemical cleaning protocol gave the highest cleaning efficiency since both reversible fouling and most of irreversible fouling was removed. When only chemicals alone were used, the sodium tripolyphosphate seemed to be the most effective reagent for both membranes with and without the LSMM additive. Overall, the incorporation of the LSMM additive did not statistically enhance cleaning efficiency.
Keywords: Engineering, Environmental.